Quantum electrodynamics - Berestet︠s︡kiĭ, V. B. (Butterworth-Heinemann, 1982)
Several significant additions have been made to the second edition, including the operator method of calculating the bremsstrahlung cross-section, the calcualtion of the probabilities of photon-induced pair production and photon decay in a magnetic field, the asymptotic form of the scattering amplitudes at high energies, inelastic scattering of electrons by hadrons, and the transformation of electron-positron pairs into hadrons.
Revised edition of: Relativistic quantum theory. 1st ed. 1971-1974.
Includes index.
Keywords: Quantum electrodynamics.; elektronické knihy; electronic books